Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/02692163221129158
|View full text |Cite
|
Sign up to set email alerts
|

Determining massage dose-response to improve cancer-related symptom cluster of pain, fatigue, and sleep disturbance: A 7-arm randomized trial in palliative cancer care

Abstract: Background: The efficacy of various massage doses in palliative cancer care settings is still debated, and no specific protocol is available. Aim: Evaluating response to various massage doses for symptom cluster of pain-fatigue-sleep. Design: A 7-arm randomized-controlled trial with weekly massage for 4 weeks depending on the prescribed dose (15-, 30-, or 60-min; 2× or 3×/week) and a 4-week follow-up. The intensities of pain, fatigue, and sleep disturbance were measured using a 0–10 scale at nine-timepoint; ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Other studies in the literature have shown statistically and clinically significant effects of massage on sleep (26)(27)(28). The literature supports the results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies in the literature have shown statistically and clinically significant effects of massage on sleep (26)(27)(28). The literature supports the results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…few studies have investigated the right dosage of massage to obtain effects. A recent study has, however, looked at these effects on a population with similar objectives [ 47 ]. Future studies should clarify this question.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate to severe pain can significantly interfere with the daily life of patients [44,45]. When daily activities are disrupted, the use of assistive skills may require the support of family and friends, particularly in cases where cancer patients are experiencing pain, fatigue, and physical exhaustion [46]. The assistance of relatives and friends plays an important role in the pain management of patients [37].…”
Section: Discussionmentioning
confidence: 99%